Forced vibrations of pre-stressed sandwich plate-strip with elastic layers and piezoelectric core - Daşdemir, A. (Прикладная механика, 2018)
Within the scope of the piecewise homogeneous body model with utilizing of the three dimensional linearized theory of electro-elastic waves in initially stressed bodies, a mathematical modeling the dynamical stress field problem occurred in a sandwich platestrip is carried out. This plate consists of a piezoelectric core perfectly bonded to the elastic layers with initial stress under the action of a time-harmonic force resting on a rigid foundation. It is assumed that the piezoelectric material is poled perpendicular to free surface of the body. A governing system of the partial differential equations of motion is solved by employing the finite element method. The numerical results are presented illustrating the effect of certain dependencies of the problem on the propagations of the stresses and the electric displacements acting on the interface planes between the elastic layers and the piezoelectric core and between the plate-strip and the rigid foundation. In particular, an effect of the initial stress parameter and a change of the thickness of the piezoelectric core on the frequency response of the plate-strip is investigated.